Role of Bacterial Overgrowth in the Stomach as an Additional Risk Factor for Gastritis - Gregory Naylor; Anthony Axon (Canadian Journal of Gastroenterology)
Gastric bacteria can either be ingested or ascend from the distal bowel; however, their survival is usually limited by gastric acidity and motility. A reduction in gastric acid can result in bacterial overgrowth in the stomach and proximal small bowel, and the number of organisms rises as the intragastric pH rises.